2000
DOI: 10.1177/104973150001000603
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with Post-Traumatic Stress Disorder: The Psychological Sequelae of Bloody Sunday and the Response of State Services

Abstract: Objective This article describes the political context of health and social care services in Northern Ireland at a time of intense social conflict. Method Concepts from post-traumatic stress disorder (PTSD) and other relevant international psychological literature are then used to study the experience of the Bloody Sunday families, victims of a traumatic event that happened in Derry in January 1972. Results High levels of psychological morbidity within this population are reported, alongside some evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
0
11
1
Order By: Relevance
“…Women reported long-term effects and depression (Cairns & Mallett, 2003;Curran et al, 1990;Hayes & Campbell, 2000;McWhirter, 2002;O'Reilly & Stevenson, 2003;Potter, 2004), whereas men expressed resentment and anger (Dillenburger et al, 2007b): (My grown up children) say I have to forget him and they think I should be over it after all these years [10 years]. But I will never forget (1985/86).…”
Section: Individual Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Women reported long-term effects and depression (Cairns & Mallett, 2003;Curran et al, 1990;Hayes & Campbell, 2000;McWhirter, 2002;O'Reilly & Stevenson, 2003;Potter, 2004), whereas men expressed resentment and anger (Dillenburger et al, 2007b): (My grown up children) say I have to forget him and they think I should be over it after all these years [10 years]. But I will never forget (1985/86).…”
Section: Individual Factorsmentioning
confidence: 99%
“…With the beginning of the Peace Process, increased attention was given to victims' issues (Dillenburger et al, 2007a;Fay, Morrissey, Smyth, & Wong, 1999;Hamber, 2003;Hayes & Campbell, 2000;Kulle, 2001;Morrissey & Smyth, 2002;Northern Ireland Office, 1998;O'Reilly & Stevenson, 2003;Smyth, 1997Smyth, , 2000. After the Good Friday Agreement in 1998, victims' issues were more fully recognized (Bloomfield, 1998) and substantial support became available (Dillenburger, Akhonzada, & Fargas, 2006;McDougall, 2006): I hold the victim support group very dearly.…”
Section: Political and Cultural Contextmentioning
confidence: 99%
“…Curran et al (1990) found that immediately after the Enniskillen bombing in 1987, the GHQ-30 mean score of people who had lost a loved one, been at the scene of the bomb, or had been injured was 18.38 (SD = 6.5). Using the abbreviated GHQ-12, Hayes and Campbell (2000) found that people affected by "Bloody Sunday," 25 years after the event had a mean score of 4.9 (SD = 4.27), compared with a GHQ-12 mean score of 4.92 (SD = 4.056) for the participants in the present study.…”
Section: Cultural Measuresmentioning
confidence: 72%
“…Those living in high violence areas have been shown to experience greater levels of psychiatric distress than those in low violence areas, especially if they perceive their area as violent and dangerous (Cairns & Wilson, 1984). Moreover, personal exposure to political violence in Northern Ireland has been related to posttraumatic (Curran et al, 1990;Daly & Johnston, 2002;Hayes & Campbell, 2000;Smyth, Hayes, & Hayes, 1997) and dissociative symptoms (Dorahy, Lewis, Millar, & Gee, 2003). In addition, those directly exposed to violence or who have closer familial ties to victims report higher post-traumatic (Shevlin & McGuigan, 2003) and dissociative (Dorahy, Gilmore, Lewis, & Millar, 2000) symptoms than more distant relatives or those indirectly exposed to Troubles-related violence.…”
Section: Historical and Sociocultural Context Of Northern Irelandmentioning
confidence: 96%